Autophagy acts through TRAF3 and RELB to regulate gene expression via antagonism of SMAD proteins. Issue 1 (December 2017) - Newman, Alice; Kemp, Alain; Drabsch, Yvette; Behrends, Christian; Wilkinson, Simon
Abstract Macroautophagy can regulate cell signalling and tumorigenesis via elusive molecular mechanisms. We establish a RAS mutant cancer cell model where the autophagy geneATG5 is dispensable in A549 cells in vitro, yet promotes tumorigenesis in mice. ATG5 represses transcriptional activation by the TGFβ-SMAD gene regulatory pathway. However, autophagy does not terminate cytosolic signal transduction by TGFβ. Instead, we use proteomics to identify selective degradation of the signalling scaffold TRAF3. TRAF3 autophagy is driven by RAS and results in activation of the NF-κB family member RELB. We show that RELB represses TGFβ target promoters independently of DNA binding at NF-κB recognition sequences, instead binding with SMAD family member(s) at SMAD-response elements. Thus, autophagy antagonises TGFβ gene expression. Finally, autophagy-deficient A549 cells regain tumorigenicity upon SMAD4 knockdown. Thus, at least in this setting, a physiologic function for autophagic regulation of gene expression is tumour growth. Macroautophagy can regulate cell signalling and tumorigenesis but the molecular mechanisms are unclear. Here the authors show selective degradation of the signalling scaffold TRAF3 by autophagy and consequent activation of the NF-κB family member RELB regulate gene expression via antagonism of SMAD proteins.